Bio-profiling of TB patients with and without Type 2 Diabetes before and during anti-tuberculosis drug (ATD) therapy - Selamolela, Mosa (Stellenbosch : Stellenbosch University, 2017)
Thesis (MSc)--Stellenbosch University, 2017.